Intraluminal Farnesol and Farnesal in the Mealworm's Alimentary Canal: An Unusual Storage Site Uncovering Hidden Eukaryote Ca2+-Homeostasis-Dependent “Golgicrine” Activities - De Loof, Arnold; Schoofs, Liliane (Frontiers in Endocrinology, 2019)
Farnesol, the sesquiterpenoid precursor of the six presently known insect juvenile hormones (JHs) was for the first time chemically identified in 1961, not in JH synthesizing glands or whole body extracts, but in excrements of the mealworm Tenebrio molitor. This finding was thought to be irrelevant and remained unexplored. In 1970, it was reported that the fall to zero of the JH titer in both prediapausing adults and in last instar larvae of the Colorado potato beetle causes severe malfunctioning of the Golgi system in the fat body, among various other effects. This endomembrane system in the cytoplasm resides at the intersection of the secretory, lysosomal, and endocytic pathways and is required for the processing of secretory proteins. Why the Golgi needs farnesol-like endogenous sesquiterpenoids (FLS) for its proper functioning has also never been further investigated. In 1999 farnesol was found to be a natural endogenous ligand for particular types of voltage-gated Ca2+ channels in mammalian cells, a finding that also remained undervalued. Only since 2014 more attention has been paid to the functional research of the “noble unknown” farnesol, in particular to its Ca2+-homeostasis-related juvenilizing and anti-apoptotic activities. Here, we introduce the term “Golgicrine activity” that addresses the secretory activity of the RER-Golgi system from its role in Ca2+-homeostasis rather than from its conventional role in mere protein secretion. Golgicrine activity attributes the so far forgotten role of farnesol-like sesquiterpenoids in proper Golgi functioning, and unites the endocrine, exocrine and enterocrine functions of these sesquiterpenoids. This out of the box view may open novel perspectives for the better understanding of particular inflammatory bowel diseases and of neurodegenerative diseases as well, because the early initiation of Alzheimer’s disease may possibly result from malfunctioning of the mevalonate-farnesol-cholesterol biosynthetic pathway and thus might be a farnesol- and Ca2+-homeostasis-dependent Golgicrine issue .